An Overview of Lettuce Production Systems and Cultivars Used in Hydroponics and Protected Culture in Florida - Natalie B. Parkell; Robert C. Hochmuth; Wanda L. Laughlin (EDIS, 2015)
With correct variety selection and protected culture strategies, lettuce is a crop that can present even the novice grower with a fast-growing commodity for market sale. This 6-page fact sheet includes brief descriptions of hydroponic lettuce production systems, cultivars, and a table summarizing the lettuce types successfully grown in Florida using protected agriculture and hydroponic techniques.  It was written by Natalie B. Parkell, Robert C. Hochmuth, and Wanda L. Laughlin, and published by the UF Department of Horticultural Sciences, March 2015. (Photo: UF/IFAS)